Viral Malay Postings on Facebook: An Analysis of Content and Linguistic Attributes: (Hantaran Bahasa Melayu yang Tular di Facebook: Analisis dari Aspek Kandungan dan Atribut Linguistik) (Jurnal Bahasa, 2021)
The increasing use of Facebook among users from different walks of life has made it one of the main sources of information on social media. The extra attention given by users to Facebook posts has created a phenomenon known as "virality" in which a post can be shared with hundreds of thousands of users within a short time and much faster than the mainstream media. While previous studies have investigated viral postings from the perspective of business and mostly in the English language, this study aims to linguistically analyze Malay language postings on Facebook that cause them to go viral in terms of content and linguistic attributes. Through textual analysis of 100 Facebook postings of various topics that went viral and with a corpus size of about 10,000 words, this study captured the content and language attributes of each post and tabulate them accordingly. The results showed that the main theme of the content of viral postings is largely related to family-related advice, while the most common linguistic feature is the use of personal pronouns. In terms of writing style, it was found that argumentative and anecdotal styles are the most popular. The findings from this study have provided valuable input to content producers in creating content that would reach out to more users.